Conductivity grading in epoxy graphene oxide composites using thermal reduction. - Chatzi, Panagiota (Cranfield University, 2014)
The aim of this project is the development of a method for the production of conductivity graded polymeric materials through the in-situ reduction of Graphene Oxide (GO). These types of composites can be used for the reduction of electrical field concentrations observed in several applications, such as cables, cable joints, microelectronic components and bushings. The evolution of electrical conductivity of GO was monitored during thermal reduction under isothermal and dynamic heating thermal conditions and compared with the kinetics of the reduction reaction as observed using calorimetry. These results were replicated in epoxy/GO composite to prove the feasibility of in-situ reduction and capabilities for controlling this process. In addition, reduction was achieved in epoxy/GO composites using infrared continuous and pulsed laser. It was shown that thermal reduction is possible in the cured epoxy composite at relatively low temperatures up to 26ᴼC. The kinetics of reduction follows a double mechanism which can be represented using a double n-th order process. Electrical measurements showed that conductivity increased significantly up to 0.12 S/m for dry particles and 0.09 S/m for the composite. Heat transfer by conduction and irradiation on specific areas resulted in selective reduction, and a conductive graded material.
Keywords: Graphene oxide; thermal reduction; electrical conductivity; epoxy resin; composites; laser treatment